Taxonomic notes on Baeosega Krombein (Hymenoptera, Chrysididae), with description of two new species from southern Western Ghats, India - Binoy, C.; Mita, Toshiharu; Colombo, Wesley D.; Kumar, P. Girish (Zootaxa, 2024)
We present taxonomic updates on Baeosega Krombein, formally reporting the genus from India for the first time. We describe and illustrate two new species, B. kimseyae Binoy, Mita & Girish Kumar, sp. nov. and B. krombeini Binoy, Mita & Girish Kumar, sp. nov. from the southern Western Ghats. A key for females of the currently known species is also provided. Additionally, a distribution map of the species is included.